2021
DOI: 10.1111/1747-0080.12687
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the sports nutrition knowledge of elite Australian athletes using the Platform to Evaluate Athlete Knowledge of Sports Nutrition Questionnaire

Abstract: Aims: To evaluate the nutrition knowledge of elite Australian athletes, and to obtain feedback from sports dietitians on the Platform to Evaluate Athlete Knowledge of Sports Nutrition Questionnaires' (PEAKS-NQ) suitability.Methods: Sports dietitians from the National Institute Network across Australia recruited athletes to complete the online, 50-item PEAKS-NQ which contained two sections (General Nutrition and Sports Nutrition). Sports dietitians provided feedback on the PEAKS-NQ using a 14-item questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…When adjusting for the confounding variables (age, education, sport type and sport calibre), sex was found to influence the total score, with females performing slightly better than males (3⋅5 %). Previous studies have reported similar results, with females performing better than males (8,10,32) . For example, using the same tool, Tam et al (32) found female athletes scored 5⋅7 % higher than male athletes, while Wardle et al (10) observed females from the general population scored 4⋅4 % higher than males.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…When adjusting for the confounding variables (age, education, sport type and sport calibre), sex was found to influence the total score, with females performing slightly better than males (3⋅5 %). Previous studies have reported similar results, with females performing better than males (8,10,32) . For example, using the same tool, Tam et al (32) found female athletes scored 5⋅7 % higher than male athletes, while Wardle et al (10) observed females from the general population scored 4⋅4 % higher than males.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have reported similar results, with females performing better than males (8,10,32) . For example, using the same tool, Tam et al (32) found female athletes scored 5⋅7 % higher than male athletes, while Wardle et al (10) observed females from the general population scored 4⋅4 % higher than males. There have been various reasons suggested for this trend, including less interest among males in nutrition and also important life stages for women producing greater concern for nutrition (moving away from home, marriage, pregnancy, etc.)…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, nutrition is a key determinant of the effectiveness of recovery and adaptive responses to a training process; moreover, it has an important, if not crucial, role in health status [ 13 ]. Although optimal nutrition is the key prerequisite for sports performance, the nutrition knowledge of athletes and its impact on their dietary intake, as shown in several review and cross-sectional studies, may be lacking [ 7 , 14 , 15 ]. Furthermore, in a review article, researchers recognized that micronutrient deficiencies are common in female athletes, particularly for vitamin D, calcium, and iron [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of implementation research in the sports nutrition field may now be impeding the application of the progress made in the laboratory (Eccles and Mittman, 2006 ; Bentley et al, 2020 ). Instead, applied intervention studies remain focused on education despite an awareness that the translation of knowledge into nutrition behaviors in athletes remains imperfect (Heaney et al, 2011 ; Bentley et al, 2021 ; Foo et al, 2021 ; Tam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%